Specificity of Semiotic Organization of Internet Memes of Professional Community of Lawyers in Social Networks - A. A. Khustenko (Научный диалог)
The article deals with Internet memes that function in the professional community of lawyers in the social networks VKontakte and Odnoklassniki as a polycode text. The question is raised about the grounds for the analysis of Internet memes. The purpose of the study was to consider the semiotic organization of Internet memes of the professional community of lawyers. The relevance of the study is related to the need to study the features of speech practces determined by the forms of informal communication within such a social structure as the professional community of lawyers. The novelty of the research is seen in the development of analysis parameters that take into account the specifics of the Internet meme as a kind of polycode text, due to the peculiarity of the professional community of lawyers. An analysis of Internet memes is presented for a number of reasons. It has been established that textual memes and creolized memes, in which the text component plays a leading role, prevail quantitatively. Images in Internet memes have a high artistic and general cultural potential, which indicates a high level of the general culture of the authors and recipients of Internet memes. The semiotic analysis of Internet memes gave an idea that the professional community of lawyers significantly influences all parameters of the description of Internet memes functioning in it, which allows us to make an assumption about the existence of a specific unofficial discursive area of the corresponding professional discourse.